Pengaruh Bisnis E-Commerce dan Self Efficacy terhadap Minat Menjadi Wirausaha Mahasiswa Pendidikan Ekonomi Universitas Negeri Padang - Gia Tania Putri; Oknaryana Oknaryana (Universitas Negeri Padang, 2022)
This article purposes is to decide the effect of e-commerce business and self-confidence on one's desire to start a business of economic education students at the Padang State University. This research is a descriptive and associative used collected of data although questionnaires. The study population in research is amounted to 362 economics education student class 2017 to 2019. Sample in the study used amounted to 78 students with a error rate 10% and using technique of proportional random sampling. Data analysis used analysis of multiple regression that have previously been tested assumptions of classical. The research result shown that 1) e-commerce business has effect is significant on the interest in becoming entrepreneurs of economic education students shown from sig 0.001 <0.05. 2) self efficacy has a effect of significant on the interest in becoming entrepreneurs of economic education students shown from sig 0.000 <0.05. 3) e-commerce business and self efficacy together have a effect of significant on the interest in becoming entrepreneurs of economic education students seen from sig 0.000 <0.05.